Legal writings on contracts and disputes over contracts involving a foreign party in Vietnam = (Ho Chi Minh City Publishing House, 1993)
This book introduce about business co-opertation contracts and joint venture contracts in foreign investment in Vietnam. Bisiness contracts and economic arbitration...